Implementasi Fasilitas Rehabilitasi Medis Bagi Pengguna Narkotika di BNN Kota Mojokerto - Gaerry Amano Suitrisno; Bahrul Amiq; Yustino Yustino (Perspektif Administrasi Publik dan hukum, 2025)
Drug abuse is a serious social problem in Indonesia, including in Mojokerto City. The government, through Law Number 35 of 2009 on Narcotics, has established medical rehabilitation programs as a primary solution for handling drug users. This study aims to analyze the implementation of medical rehabilitation facilities for drug users at the National Narcotics Agency (BNN) of Mojokerto City and identify the challenges faced in its implementation. The findings indicate that the medical rehabilitation program has been carried out through various stages, including detoxification, medical therapy, and psychosocial assistance. However, several obstacles hinder its effectiveness, such as limited human resources and facilities, social stigma against drug users, and suboptimal inter-agency coordination. Therefore, improvements in facilities, medical personnel, and stigma reduction strategies are needed to support the success of rehabilitation programs for drug users.